Immunophenotypic measurable residual disease monitoring in adult acute lymphoblastic leukemia patients undergoing allogeneic hematopoietic stem cell transplantation - Tecchio, Cristina; Russignan, Anna; Krampera, Mauro (Frontiers in Oncology, 2023)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) offers a survival benefit to adult patients affected by acute lymphoblastic leukemia (ALL). However, to avoid an overt disease relapse, patients with pre or post transplant persistence or occurrence of measurable residual disease (MRD) may require cellular or pharmacological interventions with eventual side effects. While the significance of multiparametric flow cytometry (MFC) in the guidance of ALL treatment in both adult and pediatric patients is undebated, fewer data are available regarding the impact of MRD monitoring, as assessed by MFC analysis, in the allo-HSCT settings. Aim of this article is to summarize and discuss currently available information on the role of MFC detection of MRD in adult ALL patients undergoing allo-HSCT. The significance of MFC-based MRD according to sensitivity level, timing, and in relation to molecular techniques of MRD and chimerism assessment will be also discussed.